3‐Cl‐AHPC inhibits pro‐HGF maturation by inducing matriptase/HAI‐1 complex formation. Issue 1 (28th October 2018) - Ye, Fang; Chen, Shuang; Liu, Xingxing; Ye, Xiaohong; Wang, Keqi; Zeng, Zhiping; Su, Ying; Zhang, Xiao‐kun; Zhou, Hu
Abstract: Matriptase is an epithelia‐specific membrane‐anchored serine protease, and its dysregulation is highly related to the progression of a variety of cancers. Hepatocyte growth factor activator inhibitor‐1 (HAI‐1) inhibits matriptase activity through forming complex with activated matriptase. The balance of matriptase activation and matriptase/HAI‐1 complex formation determines the intensity and duration of matriptase activity. 3‐Cl‐AHPC, 4‐[3‐(1‐adamantyl)‐4‐hydroxyphenyl]‐3‐chlorocinnamic acid, is an adamantly substituted retinoid‐related molecule and a ligand of retinoic acid receptor γ (RARγ). 3‐Cl‐AHPC is of strong anti‐cancer effect but with elusive mechanisms. In our current study, we show that 3‐Cl‐AHPC time‐ and dose‐ dependently induces matriptase/HAI‐1 complex formation, leading to the suppression of activated matriptase in cancer cells and tissues. Furthermore, 3‐Cl‐AHPC promotes matriptase shedding but without increasing the activity of shed matriptase. Moreover, 3‐Cl‐AHPC inhibits matriptase‐mediated cleavage of pro‐HGF through matriptase/HAI‐1 complex induction, resulting in the suppression of pro‐HGF‐stimulated signalling and cell scattering. Although 3‐Cl‐AHPC binds to RARγ, its induction of matriptase/HAI‐1 complex is not RARγ dependent. Together, our data demonstrates that 3‐Cl‐AHPC down‐regulates matriptase activity through induction of matriptase/HAI‐1 complex formation in a RARγ‐independent manner, providing a mechanism of 3‐Cl‐AHPC anti‐cancer activity and a new strategy to inhibit abnormal matriptase activity via matriptase/HAI‐1 complex induction using small molecules.